Political Connections and Preferential Access to Finance: The Role of Campaign Contributions - Claessens, Stijn (2012)
Using novel indicators of political connections constructed from campaign contribution data, we show that Brazilian firms that provided contributions to (elected) federal deputies experienced higher stock returns than firms that did not around the 1998 and 2002 elections. This suggests that contributions help shape policy on a firm-specific basis. Using a firm fixed effects framework to mitigate the risk that unobserved firm characteristics distort the results, we find that contributing firms substantially increased their bank financing relative to a control group after each election, indicating that access to bank finance is an important channel through which political connections operate. We estimate the economic costs of this rent seeking over the two election cycles to be at least 0.2% of gross domestic product per annum.